Prevalence of Preeclampsia in Brazil: An Integrative Review - Guida, José Paulo de Siqueira; Andrade, Beatriz Gadioli de; Pissinatti, Luis Gabriel Ferreira; Rodrigues, Bruna Fagundes; Hartman, Caio Augusto; Costa, Maria Laura (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To review literature and estimate the occurrence of preeclampsia and its complications in Brazil.Methods We performed an integrative review of the literature, and included observational studies published until August 2021 on the SciELO and PubMed databases that evaluated preeclampsia among pregnant women in Brazil. Other variables of interests were maternal death, neonatal death, hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome, and eclampsia. Three independent reviewers evaluated all retrieved studies and selected those that met inclusion criteria. A metanalysis of the prevalence of preeclampsia and eclampsia was also performed, to estimate a pooled frequency of those conditions among the studies included.Results We retrieved 304 studies after the initial search; of those, 10 were included in the final analysis, with a total of 52,986 women considered. The pooled prevalence of preeclampsia was of 6.7%, with a total of 2,988 cases reported. The frequency of eclampsia ranged from 1.7% to 6.2%, while the occurrence of HELLP syndrome was underreported. Prematurity associated to hypertensive disorders ranged from 0.5% to 1.72%.Conclusion The frequency of preeclampsia was similar to that reported in other international studies, and it is increasing in Brazil, probably due to the adoption of new diagnostic criteria. The development of a national surveillance network would be essential to understand the problem of hypertensive disorders of pregnancy in Brazil.
Keywords: preeclampsia; epidemiology; Brazil